Issledovanie psichofiziologicheskich osobennostej lyŽnikov-gonŠcikov i biatlonistov podrostkovogo vozrasta - Nenenko, N. D.; Astrachancev, A. A. (International Research Journal, 2019)
In this paper, we evaluate the psychophysiological status of teenager athletes in racing skiing and biathlon during the competitive period. Adolescent biathletes are superior compared to their peers who specialized in skiing in terms of speed of a simple sensory-motor reaction and the speed of a discrimination reaction; in addition, young biathletes were more accurate in completing tasks in both tests (Whipple coefficient). The revealed features of the psychophysiological status of winter sports teenagers can serve as informative criteria for the retraining of skiers to biathlon.